Still going strong at 40 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Tidiani Diarra talked to Spore s Eyoum Ngangué about the metamorphosis of Malian farmers organisations.